Dietary protein score and carbohydrate quality index with the risk of chronic kidney disease: Findings from a prospective cohort study - Teymoori, Farshad; Farhadnejad, Hossein; Jahromi, Mitra Kazemi; Vafa, Mohammadreza; Ahmadirad, Hamid; Mirmiran, Parvin; Azizi, Fereidoun (Frontiers in Nutrition, 2022)
Background/aim: This study aimed to examine the associations between dietary protein score and carbohydrate quality index (CQI) and the risk of chronic kidney disease (CKD) in Iranian adults. Methods: This population-based cohort study was performed within the Tehran Lipid and Glucose Study framework on 6044 subjects aged≥18 years old, who were followed up for a mean of 7.7 years. Dietary protein score and CQI were determined using a food frequency questionnaire. CKD was defined as an estimated glomerular filtration rate<60 ml/min/1.73 m2. A multivariate Cox proportional hazard regression model was used to estimate the risk of CKD across tertiles of protein score and CQI. Results: The mean (standard deviation) of age and body mass index of participants were 37.9(12.8) years and 26.8(4.7) kg/m2, respectively. During the 7.7±2.7 years of follow-up, 1216 cases (20.1%) of CKD were ascertained. In the final adjusted model, individuals in the highest tertile of protein score had decreased risk of CKD (HR: 0.85, 95% CI: 0.74-0.98,Ptrend=0.033). Also, there is a significant association between total carbohydrate score (HR:0.85,95%CI:0.73-0.99,Ptrend=0.016), the ratio of whole grain/total grains (HR:0.81,95%CI:0.70-0.94,Ptrend=0.004), and glycemic index (HR:1.30,95%CI:1.12-1.51,Ptrend<0.001) and risk of CKD. However, no significant association was found between total protein intakes, plant-to-animal ratio, and solid carbohydrate/total carbohydrate with the risk of CKD. Conclusion: Our results revealed a diet with a high protein score and high quality of carbohydrates, characterized by higher intakes of plant proteins, low GI carbohydrates, whole grain, fibers, and lower intakes of animal proteins, can be related to reduced CKD risk.